Effects of Zinc Oxide Nanoparticles (ZnO NPs) Synthesized from River Oak Casuarina cunninghamiana Miq.,1848 Leaf Extracts on Three Insects Species - Omar, Saher T.; Ali, Wand K. (Iraqi Journal of Science, 2024)
Despite the widespread use of zinc oxide nanoparticles (ZnO NPs) in various fields, there have been a growing number of reports regarding their toxicity. However, there is insufficient research available regarding the insecticidal effects of ZnO nanoparticles. Using leaves of the river oak tree (Casuarina cunninghamiana Miq., 1848), this study aimed to produce ZnO NPs utilizing a simple and eco-friendly biological process to evaluate the toxic effects of zinc oxide nanoparticles on the mealworm (Tenebrio molitor Fabricius, 1792), the superworm (Zophobas atratus Fabricius, 1775) and the red flour beetle (Tribolium castaneum Herbst, 1797). The produced zinc oxide nanoparticles were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM) and UV-visible spectroscopy. The laboratory study was conducted by feeding larvae with leaves immersed in a solution of different concentrations of zinc oxide nanoparticles. The lethal effects of the nanoparticles on the three studied insects were recorded at different time intervals. The outcomes of the statistical analysis displayed important differences in the mean mortality rate according to the composition of the zinc particles and the insects. The highest overall average larval mortality rate was 31.6% among the studied insects with 51.40% being the overall average adult emergence success rate of the studied insect larvae. The LC50 values of the extracted zinc oxide nanoparticles from the used plant, on the other hand, showed varying effects on the mealworm larvae, with a value of 396.27 parts per million (ppm). While the values for the super worm larvae were 6760.83 ppm and that for the red flour beetle larvae the values were 977.23 ppm. These results suggested that the synthesized zinc oxide nanoparticles from river oak tree leaves possess lethal properties against larvae and adults, making them an alternative to synthetic insecticides in insect control stages and environment friendly. Therefore, biologically derived zinc oxide nanoparticles can be used as a potential agent for insect control.